Customs and Culture in Poland under the Last Saxon King : Selections from Opis obyczajów za panowania Augusta III by father Jędrzej Kitowicz, 1728-1804 - Kitowicz, Jędrzej (Book collections on Project MUSE., 2019)
"Jedrzej Kitowicz was a parish priest in central Poland with a military and worldly past. In his later years, after putting the affairs of his parish in order, he composed a colorful chronicle of all aspects and walks of life under King August III. He seems to have written mostly from memory, creating in the process the most complete record that exists of society in eighteenth-century Poland. A man with omnivorous tastes, a keen sense of observation, and a wry--at times bawdy--sense of humor, Kitowicz's realistic and robust literary technique has been compared in its earthiness and evocativeness to Flemish genre painting. A noteworthy example of eighteenth-century writing and narrative talent, his Opis reveals an astounding visual memory and a modern ethnographer's eye for material culture. The present book consists of fifty-one chapters, including all of the most celebrated ones, from Father Kitowicz's Opis, complete with a comprehensive introduction. Topics include religious beliefs, customs and institutions, child-rearing, education, the judiciary and the military. Particularly vivid are the descriptions of the lives of the nobility, ranging from cooking through men's and women's wear to household entertainments and drinking habits. A commentary by the editor introduces each chapter"--